Medical insurance and health equity in health service utilization among the middle-aged and older adults in China: a quantile regression approach - Guorui Fan; Zhaohua Deng; Xiang Wu; Yang Wang (BMC, 2020)
Abstract Background China has achieved nearly universal coverage of the Social Basic Medical Insurance (SBMI), which aims to reduce the disease burden and improve the utilization of health services. We investigated the association between China's health insurance schemes and health service utilization of middle-aged and older adults at different quantiles, and then explored whether the SBMI could help reduce the underutilization of health services among the middle-aged and older adults in China. Methods Survey data of middle-aged and older adults were drawn from the China Health and Retirement Longitudinal Study (CHARLS). A linear quantile mixed regression model was utilized to provide a comprehensive understanding of the relationship between SBMI and health service utilization, which was measured by the total medical expenditure. We took the New Rural Cooperative Medical Scheme (NCMS) as the reference level and examined the associations of the Urban Employee Basic Medical Insurance (UEBMI) and the Urban Resident Basic Medical Insurance (URBMI) with health service utilization. Results The quantile regression analysis revealed a significant positive association between URBMI and health service utilization at the 0.75 (β = 1.608, p < 0.01), 0.8 (β = 1.578, p < 0.01), 0.85 (β = 1.473, p < 0.01), 0.9 (β = 1.403, p < 0.01) and 0.95 (β = 1.152, p < 0.01) quantiles, and also a significant positive association between UEBMI and health service utilization at the 0.85 (β = 1.196, p < 0.01), 0.9 (β = 1.070, p < 0.01) and 0.95 (β = 0.736, p < 0.01) quantiles. Results showed that URBMI was significantly associated with an improvement in inpatient health service utilization of the middle-aged and older adults, and a significant positive association between UEBMI and inpatient health service utilization was observed at 0.1 (β = 0.559, p < 0.01), 0.25 (β = 0.420, p < 0.05), 0.5 (β = 0.352, p < 0.05), and 0.75 (β = 0.306, p < 0.05) quantiles. Conclusions Inequity in health service utilization exists among the middle-aged and older adults across urban and rural Chinese areas, and it can be explained by the different reimbursement benefits of SBMI types.